MiR-136 Modulates TGF-β1-Induced Proliferation Arrest by Targeting PPP2R2A in Keratinocytes. (14th January 2015) - Zhang, Dianbao; Wang, Jing; Wang, Zhe; Zhang, Tao; Shi, Ping; Wang, Xiliang; Zhao, Feng; Liu, Xiaoyu; Lin, Xuewen; Pang, Xining
Abstract : Keratinocytes proliferation is critical for the capacity to heal wounds and accumulating evidences have proved that dysregulation of microRNAs is involved in proliferation of keratinocytes. However, the molecular mechanisms remain to be completely elucidated. Here, we show that miR-136 was significantly decreased by TGF- β 1 treatment in HaCaT cells and normal human epidermal keratinocytes (NHEK), and it was a Smad3-dependent manner. By cell proliferation assay and cell cycle analysis, we found that reintroduction of miR-136 by transfection, as well as PPP2R2A silencing, counteracted TGF- β -induced proliferation arrest in HaCaT cells. Further, PPP2R2A was verified as a direct target of miR-136 by dual-luciferase reporter assays and Western blotting. These data suggest that miR-136 may play an important role during TGF- β 1-induced proliferation arrest by targeting PPP2R2A in keratinocytes, which might represent a potential target for improving skin wound healing.